Empowerment of Housewife in Planting and Use Of Family Medicine Plants (Toga) - Oky Ristya Trisnawati (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2019)
Utilization of natural materials that have the potential as medicine in the yard of people's housesmotivated by a correct understanding of herbal medicine or medicinal plants family (TOGA) which is commonly known as a living pharmacy. However, knowledge and the knowledge of the Kaliwungu Village community about family medicinal plants (TOGA) is still less, so that people are less able to utilize their home yards for farming cultivating medicinal plants. Implementation of socialization and provision of training Utilization and cultivation of family medicinal plants (TOGA) is one of the ways effective and doable to preserve culture to cultivate and use medicinal plants. This research activity was carried out with a purpose to: (1) provide scientific knowledge about the types and efficacy of TOGA to housewives in Kaliwungu Village, (2) providing knowledge about procedures planting TOGA for housewives in Kaliwungu Village, and (3) giving knowledge to process TOGA for housewives in Kaliwungu Village. Activity research in Kaliwungu Village, Klirong District, Kebumen Regency was conducted for 2 (two) days, namely Monday, December 24 2018 and Sunday, December 23December 2018 using lecture, demonstration and discussion methods. The implementation of this research activity can be described through 3 (three) stages of activity, namely preparation, implementation and evaluation. The real results obtained after the implementation this family medicine cultivation training program (TOGA) is knowledge enhancement the people of Kaliwungu Village in particular are housewives from RT 01 RW 04 and RT 02 RW 04 regarding types, benefits, methods of processing or utilization and methods of planting TOGA.